Musaqah Practices In Palm Palm Gardening Sharia Economic Legal Perspective In Sabaran Village, South Jawai District - fiky (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2024)
This research was motivated by an agreement made by several oil palm farmers in Sabaran village, where in this agreement there were deviations from the agreement that had been agreed and the agreement made did not fulfill the terms of the musaqah contract. In particular, land maintenance is considered less than optimal by the land owner so that the harvest results are not optimal. In Sharia Economic Law, based on the pillars and terms of musaqah, agreements made do not have a time limit for when the agreement ends. So the form of cooperation carried out no longer meets the requirements This research method uses qualitative methods with field research. This research uses a sociological (empirical) approach, because research using qualitative methods and a sociological (empirical) approach can more easily describe the conditions and situations that occur in the field, namely in Sabaran village, South Jawai subdistrict. To obtain data, researchers used field observation and interview methods. Based on the research results obtained, it can be concluded that 1) the practice of musaqah for oil palm plantations in Sabaran village, South Jawai District, land owners feel that the results obtained are not optimal due to lack of maintenance. Meanwhile, land managers find it difficult to maintain palm oil optimally considering high fertilizer prices and fluctuating palm oil prices. This happens because of miscommunication between the parties making the agreement and a lack of knowledge about the agreement being made. 2). Based on the terms of musaqah, in practice the musaqah of oil palm plantations in Sabaran village is not running as it should. Due to a lack of knowledge regarding the agreement being made as well as miscommunication between the parties making the agreement. So the results obtained do not match the expectations of both parties. One of the conditions in the practice of musaqah is not fulfilled, namely the deadline for the end of the contract, in practice this condition is not carried out by both parties